Research Progress of Solid Electrolytes in Solid-State Lithium Batteries - Xia Nan (E3S Web of Conferences)
In today’s world where fossil fuels are increasingly depleting, electric energy, this new type of energy, is rapidly developing, the safety of batteries is receiving more and more attention from people as well. The excellent mechanical properties of solid-state batteries significantly enhance their safety features. However, the mainstream solid-state inorganic electrolytes and gel polymer electrolytes still face issues such as low ionic conductivity, poor electrode interface performance, and inadequate environmental stability. This paper is based on years of research by predecessors on the characteristics of Solid inorganic electrolytes and gel polymer electrolytes, summarizing the recent research progress on solid-state composite electrolytes by researchers, discussing the properties of single-phase electrolytes and the improvement of composite-phase electrolytes. It discusses the improvement of solid-state battery performance by solid-state composite electrolytes from three aspects: polymer composite non-polar ceramic materials, the addition of SN catalysts, and three-dimensional skeletal structures. It analyses the problems and challenges of solid-state electrolytes, Pointing out the existing shortcomings of the current solid composite electrolytes. Finally, providing directions for the continued development of solid-state electrolytes.